Doppler tissue imaging to assess systolic function in Chagas' disease - Barros,Márcio Vinícius Lins (2003)
OBJECTIVE: To assess the usefulness of Doppler tissue imaging (DTI) for evaluating the systolic function of chagasic patients with and without electrocardiographic abnormalities, in comparision with echocardiographic study. METHODS: We studied 77 patients divided into 3 groups as follows: group 1 - control; group 2 - chagasic patients with normal electrocardiographic findings; and group 3 - chagasic patients with abnormal electrocardiographic findings. The following parameters were assessed: left ventricular dimensions and ejection fraction, left atrial dimensions and diastolic function on echocardiography. Systolic velocity and regional isovolumic contraction time (IVCTr) of the septal, anterior, lateral, posterior and inferior left ventricular walls were assessed on DTI. RESULTS: Left ventricular cavitary dimensions, ejection fraction and DTI systolic wave showed significant differences between groups 1 and 3 and between groups 2 and 3, which were not found between groups 1 and 2. IVCTr allowed a statistically significant discrimination among the 3 groups. CONCLUSION: DTI allowed discrimination among the different groups assessed, being superior to echocardiography in identifying early abnormalities of contractility, and, therefore, potentially useful for detecting incipient myocardial alterations in chagasic patients with normal electrocardiographic findings.